Reactivity of Grubbs–Hoveyda II Complexes Including Extended N-Heterocyclic Carbenes with a Bicyclic Camphor-Based Framework - Rais, Eduard; Flörke, Ulrich; Wilhelm, René (Synthesis, 2017)
This feature article discusses the synthesis of new asymmetric Grubbs–Hoveyda II complexes with extended N-heterocyclic carbenes containing a bicyclic camphor-based framework. The new enantiopure complexes can be prepared in a short route from the chiral pool. The extended carbene-based catalyst shows high activity in olefin metathesis reactions. The new complexes exhibited enantioselectivity in an asymmetric ROCM desymmetrization. Depending on the substituents on the nitrogen atoms of the carbenes, the opposite enantiomer was formed in excess.
Keywords: N-heterocyclic carbenes; ruthenium; asymmetric catalysis; metathesis; camphor